Scenarios in the development strategies of larger cities in Poland - Sołtys, Jacek (Scenariusze w strategiach rozwoju większych miast w Polsce, 2019)
Planning prepares decisions and future actions. Therefore, future conditions should be considered in planning, in particular strategic planning, due to its long-term nature. To accomplish this, certain prognostic methods should be applied. A scenario method is seen as one of the most useful prognostic method, especially in cases when social and institutional behaviour plays a crucial role. The aim of the paper is an analysis and evaluation of the application of scenarios in the development strategies of larger cities in Poland (more than 100 thousand inhabitants). Scenarios were prepared in 13 out of the 39 cities. All these scenarios were analyzed. The scenarios were formulated with the intuitive logics method. Most scenarios do not fully meet the scenario definition because of the insufficiency of the sequences of events presented on the timeline. The author discusses some methodological problems concerning the creation of scenarios and the problems in using scenarios, and gives some recommendations
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2019; vol. 63, nr 2, s. 91-100
Keywords: cities; development strategy; forecasting; scenarios; strategic planning; miasta; strategia rozwoju; prognozowanie; scenariusze; planowanie strategiczne